DIFFICULTIES OF TRANSLATING CLOTHING NAMES IN UZBEK AND ENGLISH (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article examines the difficulties in translating clothing names in Uzbek and english languages. In translation linguistics, the process of translating cultural lexical units, in particular clothing terms, is a complex process depending on various cultural differences and national dress traditions. The article discusses cultural differences, the influence of climate and geographical conditions, and national and semantic differences in clothing names as the main difficulties. Ways to overcome these problems are presented through descriptive translation and cultural equivalents